After disaster : agenda setting, public policy, and focusing events - Birkland, Thomas A. (American governance and public policy., 1997)
Examines how disasters like earthquakes, oil spills, and nuclear power plant accidents can act as focusing events "which cause both citizens and policymakers to pay more attention to a public problem and often to press for solutions ... Explains how and why some public disasters change political agendas and, ultimately, public policies."--Page 4 of cover